The Dynamics of Parasocial Relationships in the Age of Social Media: A Systematic Review and Future Research Agenda - Muhmin, Andi Hidayat; Syah, Tantri Yanuar Rahmat; Anggraeni, Adilla (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
Examining the evolving dynamics of parasocial relationships (PSRs) in social media, this in-depth systematic literature review utilizes the TCM framework to analyze 40 articles. The goal is to evaluate the influences on the development and persistence of PSRs and the one-sided bonds individuals create with media personalities. The importance of source credibility, attractiveness, and interactivity in promoting PSRs is emphasized in the research findings. These factors can influence consumer behaviors, brand attitudes, and psychological well-being. Quantitative methods were mainly used in the research, and the most studied platform was Instagram, while the most widely used framework was the source credibility theory. The review underscores the need for further research to explore the long-term implications of PSRs, the impact of emerging technologies, and ethical considerations in influencer marketing, advocating for a multi-method approach to understand the complexities of PSRs in the digital age.